Constant Pressure-controlled Extrusion Method for the Preparation of Nano-sized Lipid Vesicles - Morton, Leslie A. (MyJove Corporation, 2012)
Liposomes are artificially prepared vesicles consisting of natural and synthetic phospholipids that are widely used as a cell membrane mimicking platform to study protein-protein and protein-lipid interactions(3), monitor drug delivery(4,5), and encapsulation(4). Phospholipids naturally create curved lipid bilayers, distinguishing itself from a micelle.(6) Liposomes are traditionally classified by size and number of bilayers, i.e. large unilamellar vesicles (LUVs), small unilamellar vesicles (SUVs) and multilamellar vesicles (MLVs)(7). In particular, the preparation of homogeneous liposomes of various sizes is important for studying membrane curvature that plays a vital role in cell signaling, endo- and exocytosis, membrane fusion, and protein trafficking(8). Several groups analyze how proteins are used to modulate processes that involve membrane curvature and thus prepare liposomes of diameters <100 - 400 nm to study their behavior on cell functions(3). Others focus on liposome-drug encapsulation, studying liposomes as vehicles to carry and deliver a drug of interest(9). Drug encapsulation can be achieved as reported during liposome formation(9). Our extrusion step should not affect the encapsulated drug for two reasons, i.e. (1) drug encapsulation should be achieved prior to this step and (2) liposomes should retain their natural biophysical stability, securely carrying the drug in the aqueous core. These research goals further suggest the need for an optimized method to design stable sub-micron lipid vesicles. Nonetheless, the current liposome preparation technologies (sonication(10), freeze-and-thaw(10), sedimentation) do not allow preparation of liposomes with highly curved surface (i.e. diameter <100 nm) with high consistency and efficiency(10,5), which limits the biophysical studies of an emerging field of membrane curvature sensing. Herein, we present a robust preparation method for a variety of biologically relevant liposomes. Manual extrusion using gas-tight syringes and polycarbonate membranes(10,5) is a common practice but heterogeneity is often observed when using pore sizes <100 nm due to due to variability of manual pressure applied. We employed a constant pressure-controlled extrusion apparatus to prepare synthetic liposomes whose diameters range between 30 and 400 nm. Dynamic light scattering (DLS)(10), electron microscopy(11) and nanoparticle tracking analysis (NTA)(12) were used to quantify the liposome sizes as described in our protocol, with commercial polystyrene (PS) beads used as a calibration standard. A near linear correlation was observed between the employed pore sizes and the experimentally determined liposomes, indicating high fidelity of our pressure-controlled liposome preparation method. Further, we have shown that this lipid vesicle preparation method is generally applicable, independent of various liposome sizes. Lastly, we have also demonstrated in a time course study that these prepared liposomes were stable for up to 16 hours. A representative nano-sized liposome preparation protocol is demonstrated below.